Discourse Analysis: The Use of Sentence and Phrase Templates in Food Endorsements by Instagram Influencers - Boris Ramadhika (Kusuma Negara Business School, 2020)
This study aims to analyze the hidden meaning of the sentences that are used frequently by the Instagram influencer of @jogjataste to promote the products. It was a qualitative research study with the focus on understanding and an emphasis on meaning. Analysis using discourse analysis approach was used to define the hidden meaning from the data which were 5 sentence templates used by the influencer. It is found that the influencer tends to use simple and elliptical sentences. This may due to the limited time in the Instagram story feature which only has 15 seconds. Those sentence forms are supported by the use of exclamatory sentences which are the most frequently used form to promote the foods as this kind of form shows how the speaker feels. This is to make the endorsement more interesting as the dictions such as sumpah and jujur can really affect followers’ interests on the foods psychologically.